2021
DOI: 10.1111/cas.15227
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput and multi‐phases identification of autoantibodies in diagnosing early‐stage breast cancer and subtypes

Abstract: Autoantibodies (AAbs) targeted tumor‐associated antigens (TAAs) have the potential for early detection of breast cancer. Here, 574 early‐stage breast cancer (ES‐BC) patients containing 4 subtypes (Luminal A, Luminal B, HER2+, TN), 126 benign breast disease (BBD) patients, and 199 normal healthy controls (NHC) were separated into three‐phases to discover, verify, and validate AAbs. In discovery phase using high‐throughput protein microarray, 37 AAbs with sensitivity of 31.25%‐86.25% and specificity over 73% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Recently, Rongrong Luo et al identified five autoantibodies whose concentration differed in the serum of patients with different subtypes of breast cancer. The panel composed of the five autoantibodies can be used to discern triple-negative breast cancer from non-triple-negative breast cancer, and the AUC is 0.875 (63). At present, the specific mechanism of various autoantibodies and their corresponding antigens in the occurrence and development of breast cancer remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rongrong Luo et al identified five autoantibodies whose concentration differed in the serum of patients with different subtypes of breast cancer. The panel composed of the five autoantibodies can be used to discern triple-negative breast cancer from non-triple-negative breast cancer, and the AUC is 0.875 (63). At present, the specific mechanism of various autoantibodies and their corresponding antigens in the occurrence and development of breast cancer remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of cyri-b in the pancreas, in concert with expression of KRAS G12D and p53 R172H led to acceleration of PanIN formation and an increase in the area of pancreas showing lesions with high phospho-ERK and Phospho-JNK, two crucial downstream targets of KRAS and RAC1 that drive proliferation and expansion. Other recent studies implicated CYRI-B (Fam49B) autoantibodies as a potential biomarker for early stage breast cancer (Luo et al , 2022), a gene found in patient serum on extrachromosomal circular DNA overexpressed in lung adenocarcinoma (Xu et al , 2022b) and a potential saliva marker of oral cancer (Kawahara et al , 2016). CYRI-B was also highlighted as a target of the zinc finger RNA-binding protein Zfrbp, leading to accelerated tumour development when overexpressed in colorectal and liver cancers (Long et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of CYRI-B in mice with PDAC suggested that it would be worth autoantibodies as a potential biomarker for early stage breast cancer (Luo et al, 2022), a gene found in patient serum on extrachromosomal circular DNA overexpressed in lung adenocarcinoma (Xu et al, 2022b) and a potential saliva marker of oral cancer (Kawahara et al, 2016). CYRI-B was also highlighted as a target of the zinc finger RNA-binding protein Zfrbp, leading to accelerated tumour development when overexpressed in colorectal and liver cancers (Long et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the discovery phase, the human proteome high‐density antigen microarray (HuProt version 3.1; CDI Labs, Mayaguez, Puerto Rico), which contains ∼21,000 proteins covering 81% of open reading frame region proteins of the human genome, was used. The standard procedure was identical to the procedure in our previous study 21 . Detailed experimental procedures are shown in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…In validation phase 1, candidate proteins N4BP1 and UBAP2 with a glutathione transferase tag (CDI Labs) were purified from yeast, along with the synthesis of candidate proteins CREB1 and DEAF1 with a histidine 6 tag via the same method. The standard ELISA procedure is described in our previous studies 21 . It is provided in Table S3.…”
Section: Methodsmentioning
confidence: 99%